2021
DOI: 10.1016/j.canrad.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Mise en place de la dématérialisation du dossier patient dans un contexte de COVID dans les services de radiothérapie de l’ONCORAD : passage « au sans papier »

Abstract: Les dossiers patients sous format papier ont clairement été identifiés comme vecteurs favorisant la transmission rapide du SARS-CoV-2 ( Severe Acute Respiratory Syndrome Coronavirus 2 ) entre patient/personnel et personnel/personnel. Pour pallier ce problème, les services de radiothérapie du groupe ONCORAD ont travaillé sur une méthodologie pour la dématérialisation totale du dossier patient, basée sur une démarche qualité, dans un délai de trois semaines. Ce travail a permis une amélior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…is most often carried out by direct contact (face to face) as shown in the statistics in (Figure 3) a study has shown that the transition to "paperless" has enabled us to signifi cantly reduce the risk of contamination of the covid-19 when exchanging documents from hand to hand. (7) On the other hand, the majority (82%) of these interviews never participated in a remote meeting organized by their managers during this pandemic, while 18% rarely participated in such meetings.…”
Section: Ict Usage: Professional To Professionalmentioning
confidence: 97%
See 1 more Smart Citation
“…is most often carried out by direct contact (face to face) as shown in the statistics in (Figure 3) a study has shown that the transition to "paperless" has enabled us to signifi cantly reduce the risk of contamination of the covid-19 when exchanging documents from hand to hand. (7) On the other hand, the majority (82%) of these interviews never participated in a remote meeting organized by their managers during this pandemic, while 18% rarely participated in such meetings.…”
Section: Ict Usage: Professional To Professionalmentioning
confidence: 97%
“…Numerous measures have been decided to escape the inexorable advance of the new coronavirus, qualified as a pandemic by the WHO. (6) Faced with this situation of confinement of the population, the use of ICT is a necessity today more than ever in order to improve access to health care, increase the efficiency of interventions, reduce barriers to participation, improve adherence to treatment.... (7) In this perspective, this study aims at testing the following hypothesis: "Increase of the use of the ICT in the hospitals equals decrease of the cases contaminated by the coronavirus". In order to assess the following points:…”
Section: Introductionmentioning
confidence: 99%